Geometry Optimisation of a Wave Energy Converter - Susana Costa; Jorge Ferreira; Nelson Martins (Energies)
The geometry optimisation of a point-absorber wave energy converter, focusing on the increase in energy absorption derived from heave forces, was performed. The proposed procedure starts by developing an initial geometry, which is later evaluated in terms of hydrodynamics and optimised through an optimisation algorithm to tune the shape parameters that influence energy absorption, intending to obtain the optimal geometry. A deployment site on the Portuguese coast was defined to obtain information on the predominant waves to assess several sea states. NEMOH and WEC-Sim (both open-source software packages) were used to evaluate the interaction between the structure and the imposed wave conditions. The results extracted and analysed from this software included forces in the six degrees of freedom. Under extreme wave conditions, the highest increase in the relative capture width between the initial and final shapes was around 0.2, corresponding to an increase from 0.36 to 0.54, while under average wave conditions, the increase only reached a value of around 0.02, corresponding to an increase from 0.22 to 0.24, as calculated through the relative capture width values.